Entrepreneurship for Sustainability: Dampak Education Sustainability dan Awareness of Green Accounting - Julita, Julita; Desmiyawati, Desmiyawati; Natariasari, Riska; Luthfi Iznillah, Muhammad; Nabila, Kania; Izzara, Aidura (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2025)
This study investigates the influence of Education Sustainability on Entrepreneurship for Sustainability, moderated by Awareness of Green Accounting, among university students. The topic is critical as higher education plays a pivotal role in shaping sustainable entrepreneurial practices aligned with the Sustainable Development Goals (SDGs). Conducted at Universitas Riau, Indonesia, the research adopts a causal design with data collected via a digital questionnaire distributed to students enrolled in entrepreneurship courses. A sample of 753 respondents was selected through convenience sampling. The data were analyzed using Partial Least Square-Structural Equation Modeling (PLS-SEM), ensuring robust testing of complex models. Results reveal that Education Sustainability significantly impacts Entrepreneurship for Sustainability, with Awareness of Green Accounting functioning as both a direct predictor and a quasi-moderator. These findings emphasize the dual importance of sustainability education and green accounting awareness in fostering sustainable entrepreneurship.